Avascular Retinal Pigment Epithelial Detachment Treated With Intravitreal Ranibizumab: Three Year Follow Up - Akram, Imran; Akram, Amjad (Pakistan Journal of Ophthalmology, 2020)
Retinal pigment epithelial detachment (PED) is a common manifestation in several retinal conditions including age-related macular degeneration1. Based on retinal imaging as well as clinical examination, PEDs can be classified as drusenoid, serous or vascular2,3,4. Vascularised PEDs, as the name suggests, are associated with choroidal neovascularization (CNV). Drusenoid and serous PEDs may or may not have an associated CNV. Anti-VEGF therapy has a well proven role in the treatment of vascularized PED5,6. Less well established is the beneficial effect of anti-VEGF therapy in those PEDs where a CNV is not clearly present. Large serous PEDs were excluded from phase 3 clinical trials such as TAP, ANCHOR and MARINA7,8,9 trials . As such these trials cannot be relied upon to provide management strategies for these lesions. Development of a rip in a PED can result in permanent damage to central vision10,11.Such a rip is often spontaneous although intravitreal therapy can also precipitate an RPE rip12,13. It is therefore desirable to reduce the height of a PED in order to minimize the risk of a rip. Furthermore a longstanding PED presumably interferes with the nutrition to the RPE and photoreceptors and thus early flattening of the PED or reducing its height was an important treatment rationale in this study. No universally agreed guidelines exist on the treatment of PEDs not associated with a CNV. One study14 looked specifically at the role of the anti-VEGF agent Ranibizumab (Lucentis) in non-vascularised PEDs but the follow-up period in that study was 12 months. The purpose of this study is to look at the long term effects of 3 Ranibizumab injections given in eyes with non-vascularised PEDs . The effects were monitored for up to 36 months and to date this is the longest follow-up published for this sub-set of treated patients.